A REVIEW ON THE ACTUAL INDICATIONS FOR TONSILLECTOMY IN ADULTS AND POTENTIAL POSTOPERATIVE COMPLICATIONS - Tunjai Namiq Faiq; Ozdan Akram Ghareeb (Scholar Express Journals, 2022)
Although tonsillectomy is common, its actual indications remain disputed among otolaryngologists, and it requires accuracy and skill to reduce the complications surrounding it, which may negatively affect the patient's safety. The present article aims to review the correct indications for applying tonsillectomy in adults and to describe the complications that may be experienced after surgery. The anatomy of the tonsils and the meaning of tonsillectomy were presented, focusing on the reasons for practicing tonsillectomy, and the complications associated with it. The results showed that the tonsils are part of the immune system to attack infections, and the decision to remove them should not be rushed unless when there is an actual need for it. Most important indications for tonsillectomy in adults were tonsils hyperplasia as well as recurrent tonsillitis. Hemorrhage was the most prevalent complication that could occur after tonsillectomy. It was concluded that tonsillectomy, despite its effectiveness in treating the cases required, is considered a delicate surgical operation and is not without life-threatening risks and postoperative complications, so it requires attention to the actual indications for its procedures
Keywords: Tonsillectomy; tonsils hyperplasia; recurrent tonsillitis